A abordagem temática e o ensino de física: articulações com a educação do campo - Schneider, Tatiani Maria (2017)
Researches based on the perspective of the Thematic Approach (TA) have presented a significant grow in the Sciences Education area. In this way, in the present research, the aim is to broaden the studies about the perspective of TA and possible articulations of this with the Physics Teaching, involving the context of Rural Education. In this purpose, is necessary answering the following research problem: Which comprehensions about the TA and articulation between this and the Rural Education can contribute to the construction of a formative process in schools from rural areas? In order to answer this research problem, it was realized a bibliographic review in the minutes of the Encontros de Pesquisa em Ensino de Física (EPEFs), Simpósios Nacionais de Ensino de Física (SNEFs), in the Caderno Brasileiro de Ensino de Física (CBEF) and in the Revista Brasileira de Ensino de Física (RBEF), meanly events and journals of the Physics Teaching area, besides interviews and questionnaires with teachers of the Nature Sciences area from a rural school, of the Santa Maria city. The analysis of the interviews and of the works resulting from the events and journals was realized by Textual Discursive Analysis (ATD). The results of the analysis of the articles are organized in five emergent categories: Articulation between the Thematic Approach perspective and Education in Rural Areas; The curriculum construction from Thematic Approach; Approach of themes from pre-established curriculum; The Thematic Approach and the work in classroom from the Three Pedagogical Moments; The interdisciplinary work in Thematic Approach. On the other hand, the interviews analysis result is discussed in the category: Characteristics of pedagogical practice of the teachers, defined a priori. Considering elements of these categories, a proposal of teachers’ permanent formation of a rural school is presented. The discusses carried from the production about TA in Physics Teaching area show that the interdisciplinarity and the Three Pedagogical Moments (3PM)are being used in the development of this perspective, but not all works related with TA promote changes in the curriculum. In addition, the studies about TA investigated do not establish relations with the Rural Education. With respect to rural schools, these still sound to privilege a curriculum distant of the rural reality.